Assessment of in vitro antimicrobial efficacy of biologically synthesized metal nanoparticles against pathogenic bacteria. (March 2022) - Ingle, Pramod U.; Biswas, Jayanta K.; Mondal, Monojit; Rai, Mahendra K.; Senthil Kumar, P.; Gade, Aniket K.
Abstract: The microbial infections due to biofilm forming bacterial pathogens are very common in human subjects. The intensive application of antibiotics in integrated disease management strategy has led to increased multidrug resistance incommon pathogens. Thus, indicating need of developing an alternative method for the control of these multidrug resistant pathogens. Present study involves the Moringa oleifera aqueous extract mediated biological synthesis of silver (Ag nanoparticles (NPs)- Avg. size 82.5 nm; zeta potential = −27.9 mV), copper oxide (CuONPs- Avg. size 61 nm; zeta potential = −19.3 mV), iron oxide (FeONPs- Avg. size 83.3 nm; zeta potential = −9.37 mV) and alumina (AlONPs- Avg. size 87.3 nm; zeta potential = −10.9 mV) nanoparticles. Biological nanoparticles were detected by visual observation, spectrophotometric detection followed by zeta potential analysis, nanoparticle tracking analysis, Fourier transform infrared spectrometry and X-ray diffraction analysis. Nanoparticles were further evaluated for their in vitro antimicrobial potential, membrane damage effectiveness, biofilm inhibition activity by MTT assay. Nanoparticles were assessed against human pathogens viz. two Gram-positive ( Bacillus subtilis MTCC 441 and Staphylococcus haemolyticus MTCC 3383) and two Gram-negative bacteria ( Enterobacter aerogenes MTCC 111 and Salmonella enterica ser . Typhi MTCC 8767). The nanoparticles exhibited akin activity pattern against all pathogens studied i.e. AgNPs > CuONPs > AlONPs > FeONPs. Tested nanoparticles registered lower MIC values and more intensified growth inhibition against Gram-negative bacteria compared to their Gram-positive counterparts. These results pointed out that the M. oleifera mediated nanoparticles can be prospectivelyutilized in the development of alternative antimicrobials against diverse bacterial infections. Graphical abstract: Image 1 Highlights: Ecofriendly M. oleifera mediated metal nanoparticle (NP) synthesis method reported. Antimicrobial potential of nanoparticles were assessed by inhibition assays. Bactericidal activity was monitored by Time kill assay and biofilm inhibition assay. Antibacterial activity pattern of NPs was as: AgNPs > CuONPs > AlONPs > FeONPs.